Genre Based Approach Implementation in Narrative Writing Instruction - Hanindita Putri Ashari; Dian Novita (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Writing is a fundamental component of English language learning, yet many junior high school students struggle to organize ideas and apply appropriate linguistic structures. Specific Background: The Genre-Based Approach offers a structured teaching cycle that supports students in understanding text types, purposes, and language features, particularly in narrative writing. Knowledge Gap: Although prior studies report improvements in writing performance, limited attention has been given to how teachers address practical classroom challenges during implementation. Aims: This study explores how an English teacher implemented the Genre-Based Approach in teaching narrative texts, identifies the challenges encountered, and examines the strategies used to address them. Results: Using qualitative methods through classroom observations and semi-structured interviews, the study found that the approach was applied systematically through four stages: building knowledge, modelling, joint construction, and independent construction. Major obstacles included low student learning interest and limited English vocabulary, which hindered comprehension and participation. The teacher addressed these issues using adaptive strategies such as digital media, educational games, mixed-language instruction, collaborative group work, and motivational feedback. Novelty: The research provides an in-depth classroom-level analysis of adaptive teaching practices that support Genre-Based pedagogy under real constraints. Implications: The findings underscore the importance of teacher flexibility, scaffolding, and context-responsive strategies to sustain student engagement and support writing development in EFL classrooms. Highlights: Instruction followed a sequential teaching cycle from knowledge building to independent work. Learners’ low interest and restricted vocabulary emerged as primary classroom barriers. Adaptive practices involving media, collaboration, and feedback supported student participation. Keywords: Genre-Based Approach; Narrative Writing; EFL Instruction; Teaching Strategies; Junior High School